Rotenone and elevated extracellular potassium concentration induce cell‐specific fibrillation of α‐synuclein in axons of cholinergic enteric neurons in the guinea‐pig ileum. Issue 4 (7th November 2016) - Sharrad, D. F.; Chen, B. N.; Gai, W. P.; Vaikath, N.; El‐Agnaf, O. M.; Brookes, S. J. H.
Abstract: Background: Parkinson's disease is a progressive neurodegenerative disorder that results in the widespread loss of select classes of neurons throughout the nervous system. The pathological hallmarks of Parkinson's disease are Lewy bodies and neurites, of which α‐synuclein fibrils are the major component. α‐Synuclein aggregation has been reported in the gut of Parkinson's disease patients, even up to a decade before motor symptoms, and similar observations have been made in animal models of disease. However, unlike the central nervous system, the nature of α‐synuclein species that form these aggregates and the classes of neurons affected in the gut are unclear. We have previously reported selective expression of α‐synuclein in cholinergic neurons in the gut ( J Comp Neurol . 2013;521 :657), suggesting they may be particularly vulnerable to degeneration in Parkinson's disease. Methods: In this study, we used immunohistochemistry to detect α‐synuclein oligomers and fibrils via conformation‐specific antibodies after rotenone treatment or prolonged exposure to high [K + ] in ex vivo segments of guinea‐pig ileum maintained in organotypic culture. Key Results: Rotenone and prolonged raising of [K + ] caused accumulation of α‐synuclein fibrils in the axons of cholinergic enteric neurons. This took place in a time‐ and, in the case of rotenone, concentration‐dependent manner. Rotenone also caused selective necrosis, indicated by increased cellular autofluorescence, of cholinergic enteric neurons, labeled by ChAT‐immunoreactivity, also in a concentration‐dependent manner. Conclusions & Inferences: To our knowledge, this is the first report of rotenone causing selective loss of a neurochemical class in the enteric nervous system. Cholinergic enteric neurons may be particularly susceptible to Lewy pathology and degeneration in Parkinson's disease. Abstract : Impairment of bioenergetic homeostatic mechanisms and misfolding of a‐synuclein are implicated in the pathogenesis of Parkinson's disease. Here, we show that rotenone and elevated extracellular potassium cause cell‐specific fibrillation of a‐synuclein in cholinergic enteric neurons in the guinea pig ileum. Like the central nervous system, the enteric nervous system shows selective vulnerability to stressors implicated in the pathogenesis of Parkinson's disease.